U-model based predictive control for nonlinear processes with input delay. (March 2019) - Geng, Xinpeng; Zhu, Quanmin; Liu, Tao; Na, Jing
Highlights: A general control scheme for nonlinear processes with input delay. U-model based predictive control structure. The U-model framework to represent various types of nonlinear process models. Two-degree-of-freedom control for the set-point tracking and disturbance rejection. Desired linear transfer function for the set-point tracking. Abstract: In this paper, a general control scheme is proposed for nonlinear dynamic processes with input delay described by different models, including polynomial models, state-space models, nonlinear autoregressive moving average with eXogenous inputs (NARMAX) models, Hammerstein or Wiener type models. To tackle the input delay and nonlinear dynamics involved with the control system design, it integrates the classical Smith predictor and a U-model based controller into a U-model based predictive control scheme, which gives a general solution of two-degree-of-freedom (2DOF) control for the set-point tracking and disturbance rejection, respectively. Both controllers are analytically designed by proposing the desired transfer functions for the above objectives in terms of a linear system expression with the U-model, and therefor are independent of the process model for implementation. Meanwhile, the control system robust stability is analyzed in the presence of process uncertainties. To demonstrate the control performance and advantage, three examples from the literature are conducted with a user-friendly step by step procedure for the ease of understanding by readers.